PP22 The Health of People with Past Experience of Probation Services - A Qualitative Study. (10th September 2013) - K, Lees; Parkes, J; Sinclair, J; Richards, E
Abstract : Background: A significant proportion of the UK population have had a criminal conviction (15% of 10-52 year olds). There is some evidence those in contact with probation have worse health compared to the general population. This study aimed to increase understanding of the health of people in contact with probation, through experiences of ex-offenders. The study asked the following research questions: What role do ex-offenders perceive their health plays in offending behaviour? Do ex-offenders perceive their health has changed since they were last supervised by Probation? What were ex-offenders' experiences of health interventions in probation, including Health Trainers? What perceived effect does ex-offenders' health have on those around them? Methods: Using snowball techniques to recruit, 20 participants were interviewed between June and November 2012. Interviews were semi-structured using a topic guide; recorded with participants' permission and transcribed. The transcription was coded in Nvivo and analysed using a thematic analysis. The study questions formed initial themes. Sub-themes and key concepts were developed iteratively. Results: Four themes were identified, each with sub-themes and key concepts. Theme 1 - Perceived relationship between health and offending: Substance misuse; Mental health "you need the substance to be well and you need to be well to have the strength to go thieving again." Theme 2 - Health of ex-offenders whilst offending and now: Injuries; Infectious disease; Chronic conditions; Nutrition, physical activity and body weight; Sleeping; Sexual health; Improved health since stopping offending; Substance misuse; Barriers to recovery; Mental and emotional health "I could have easily enough had a season ticket at A&E because I was always cutting myself or falling over" Theme 3 - Health interventions whilst offending: Healthcare in probation; Health trainers, mentors and peer support; Healthcare in prison; Therapeutic relationship; Service accessibility; Joined up services; Antidepressants Theme 4 - Significant others: Death and physical health; Impact on children; Domestic violence. Conclusion: Ex-offenders report a strong association between health and offending behaviour. Most perceive their current health to be much better than when they were offending. Ex-offenders reported a lack of health services whilst in probation. Their experiences of health services whilst offending highlight barriers to access and gaps in provision. Ex-offenders felt their offending behaviour had a negative impact on the health and well-being of significant others. Probation services may be an opportunity to improve the health of a population reporting poor health. Improving the health of those in probation may contribute to reducing re-offending.